The Netherlands-Indies; Rethinking post-colonial recognition from a multi-voiced perspective - Immler, Nicole L. (Wacana, Journal of the Humanities of Indonesia, 2022)
In the communication of pain, language matters. Telling someone to feel pain is not just a description of one’s pain, it is – as philosopher Ludwig Wittgenstein informs us – also asking for recognition of that pain. This requires a shared language which communicates it. Do we need a new language which can communicate and recognize the pain of the colonial past more effectively? Commencing with the recent apology for waging “a colonial war” in Indonesia by the Dutch prime minister, this article suggests an intervention in post-colonial recognition politics by exploring the idea of the multi-voicedness. Multi-voicedness (Meerstemmigheid) has become a catchword in current public and scholarly debates about the Dutch colonial past and its legacy, in which decades of recognition politics have tended to privilege clear-cut binary identities favouring certain voices above others. There is little conceptual clarity around what the term multi-voicedness entails and even less about its utility in post-colonial discourse. Although commonly associated with juxtaposing different perspectives, this article argues that introducing the lens of multi-voicedness – more specifically the idea of the dialogical self (Hubert J.M. Hermans 2004) – into the recognition discourse, contributes to a better understanding of transnational recognition politics. Capturing the diaspora’s multi-voicedness permits wider scrutiny of what is otherwise a too simplified identity and generation question implicated in post-colonial recognition politics. It will be argued that recognition claims, although supposedly part of an emancipatory struggle, are silencing the multi-voicedness of entangled Indonesian-Dutch family history, the driver for the fight for justice in the first place.